2021
DOI: 10.1172/jci.insight.139785
|View full text |Cite
|
Sign up to set email alerts
|

DMV extrasynaptic NMDA receptors regulate caloric intake in rats

Abstract: Acute high fat diet (aHFD) exposure induces a brief period of hyperphagia before caloric balance is restored. Previous studies have demonstrated this period of regulation is associated with activation of synaptic NMDA receptors (NMDARs) on dorsal motor nucleus of the vagus (DMV) neurons, which increases vagal control of gastric functions. Our aim was to test the hypothesis that activation of DMV NMDARs occurs subsequent to activation of extrasynaptic NMDA receptors (NMDARex). Sprague-Dawley rats were fed contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Rats were anesthetized with isoflurane (5% in air) before euthanized via administration of a bilateral pneumothorax. The brainstem was removed and sliced as previously described 4 . Briefly, the brainstems were excised quickly and mounted on a vibratome and submerged rapidly in cold (4°C) oxygenated Krebs’ solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were anesthetized with isoflurane (5% in air) before euthanized via administration of a bilateral pneumothorax. The brainstem was removed and sliced as previously described 4 . Briefly, the brainstems were excised quickly and mounted on a vibratome and submerged rapidly in cold (4°C) oxygenated Krebs’ solution.…”
Section: Methodsmentioning
confidence: 99%
“…A subset of 18 rats (n=9/diet from at least 2 litters) were randomly chosen to undergo gastric motility recordings as done previously 4 . Briefly, rats were fasted for 18 hours before experimentation with water available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the chronic blockade of brainstem extrasynaptic NMDA receptors blunted the HFD-induced delay in gastric emptying and significantly attenuated the homeostatic adaptation to HFD exposure for 3-5 days. Importantly, in the same study, it was shown that HFD maximally activated extrasynaptic NMDA receptors and that this effect could be mimicked by EAAT2 blockade in normal chow-fed rats [142]. Although the role played by DVC glial cells in short-term homeostatic adaptation to HFD has not yet been assessed, the mechanism revealed by Clyburn et al [142] at the DMNX glutamatergic synapses evidently suggests a decrease in astrocyte-mediated glutamate clearance as a plausible candidate to be explored in the near future.…”
Section: Open Questions and Future Avenuesmentioning
confidence: 81%
“…Importantly, in the same study, it was shown that HFD maximally activated extrasynaptic NMDA receptors and that this effect could be mimicked by EAAT2 blockade in normal chow-fed rats [142]. Although the role played by DVC glial cells in short-term homeostatic adaptation to HFD has not yet been assessed, the mechanism revealed by Clyburn et al [142] at the DMNX glutamatergic synapses evidently suggests a decrease in astrocyte-mediated glutamate clearance as a plausible candidate to be explored in the near future. Further investigation into the possible involvement of gliotransmitters in this process is also warranted.…”
Section: Open Questions and Future Avenuesmentioning
confidence: 81%
See 1 more Smart Citation